Pemahaman dan Penanaman Nilai Moderasi Beragama di Pondok Pesantren Al-Abror Kelurahan Yamansari, Kecamatan Lebaksiu, Kabupaten Tegal, Jawa Tengah - Achyar, Muhammad; Nuh HS, Moh. (Inklusiva: Jurnal Studi Agama-Agama, 2023)
Radicalism, Extremism, Terrorism in religion are problems that are still hotly discussed today, there is a group that is suspected to be one of the places where this understanding develops, namely Islamic boarding school education. This research is to answer and review in more depth that Islamic boarding school educational institutions have become a forum for education and the dissemination of understanding about moderate attitudes in religion. This research takes the form of field research which is included in the qualitative type using descriptive methods, with a sociological approach. This research uses two sources, namely primary sources which include interviews with related parties. and curriculum books, as well as secondary sources in the form of related books. Then data collection was carried out in three ways, namely: interviews with related parties, as well as literature studies and direct observation. In this research, an understanding of religious moderation was found among the Al-Abror Islamic Boarding School by looking at the four values of religious moderation, and there are two ways to instill them, namely through the role of a Kiai, and also the curriculum that is developed.